Prevalence and impact of musculoskeletal disorders of the upper limb in the general population. - Walker-Bone, K; Palmer, K; Reading, I; Coggon, D; Cooper, C (2004)
OBJECTIVE: To determine the prevalence, interrelation, and impact of musculoskeletal disorders of the upper limb in the general population. METHODS: A total of 9,696 randomly selected adults of working age were surveyed in a 2-stage cross-sectional study involving a screening questionnaire and a standardized physical examination in symptomatic subjects. Age- and sex-specific prevalence rates were estimated for several musculoskeletal disorders and for nonspecific pain in the upper limbs. The overlap and impact on daily activities and healthcare utilization were explored. RESULTS: Among 6,038 first-stage responders, 3,152 reported upper limb symptoms and 1,960 were subsequently examined. Of subjects with pain, 44.8% had 1 or more specific soft-tissue disorders. Site-specific prevalence rates were as follows: shoulder tendinitis 4.5% among men and 6.1% among women; adhesive capsulitis 8.2% among men and 10.1% among women; lateral epicondylitis 1.3% among men and 1.1% among women; de Quervain's disease 0.5% among men and 1.3% among women; other tenosynovitis of the hand or wrist, 1.1% among men and 2.2% among women. Specific disorders tended to cluster (P < 0.001) in individuals, with particular overlap at the shoulder. Compared with subjects with nonspecific pain, those with specific disorders more often reported inability to perform everyday tasks (P < 0.05), consultation with a doctor (P < 0.05), and use of prescribed medication (P < 0.05). CONCLUSION: Upper limb pain is common in the general population and is often associated with physical signs suggestive of specific upper-limb disorders. These disorders have a substantial impact on physical function and use of health care.